Description of the Psychological Condition of Pregnant Women's Husbands in the Umban Sari Community Health Center Working Area - Annisa Rahman; Misrawati Misrawati; Stephanie Dwi Guna (CV. Rayyan Dwi Bharata, 2024)
A woman's pregnancy can influence the psychological and physical health of her husband. He experiences a psychological pressure during the pregnancy period. This research aimed to find out the description of the husband’s psychological condition of the pregnant women. The design used in this reseach was descriptive research and the sampels were selected by using non-probability sampling technique with purposive sampling and gained 92 respondents as the research samples. This research employed Self-Reporting Questionnaire (SRQ)-20. The research result obtained 92 respondents, amounted 28 respondents (30,4%) were indicated with emotional disorder. The description of the cognitive symptom which was frequently experienced the most by the husband of the pregnant women was difficult in taking decision (5,45), the anxiety symptom which was mostly experienced was not sleeping well (47,8%), and the most experienced symptom of depression was crying more frequently (27,2%), the somatic symptom and the most complained was headache (43,5%), and the most symptom of energy decrease was easily tired (43,5%). Conclusion: It is important to have an early detection or screening concerning the mental health and health education program to prevent the occurrence of mental health problems on the husband of pregnant women.